Beauty as a factor of economic and social development. Issue 1 (8th January 2018) - Baggio, Rodolfo; Moretti, Vincenzo
Abstract : Purpose: The purpose of this paper is to discuss how aesthetic features can be the basis for a virtuous chain that leads to social and economic development. Design/methodology/approach: The aesthetic characteristics of a destination are an important attractive feature. More than that, they can be considered a key determinant for economic and social growth. A conceptual support to this idea is presented here by following a line which links beauty to creativity, innovation and socio-economic development. Findings: A purely qualitative and logical-deductive line shows how beauty, creativity and innovation are connected in a chain that leads to socio-economic well-being. Research limitations/implications: This paper is conceptual in nature. The authors intend to use these considerations as a basis for future research. Originality/value: This paper contributes to the literature on destination governance highlighting a number of factors that are often underestimated.